Algebraic combinatorics lectures - Orlik Peter; Summer School on Algebraic Combinatorics; Summer school on algebraic combinatorics Nordfjordeid, Norway 03-Jun (Berlin Springer-Verlag, 2007)
This book is based on two series of lectures given at a summer school on algebraic combinatorics at the Sophus Lie Centre in Nordfjordeid, Norway, in June 2003, one by Peter Orlik on hyperplane arrangements, and the other one by Volkmar Welker on free resolutions. Both topics are essential parts of current research in a variety of mathematical fields, and the present book makes these sophisticated tools available for graduate students.
Keywords: Combinatorial geometry; Free resolutions (Algebra)